Comparison of drop jump force-time profiles of team sport athletes and active controls - Thomas Scarr; Dustin J Oranchuk; Daniel Rafferty (Motriz: Revista de Educacao Fisica, 2021)
Abstract Aim: Lower-body non-contact injuries in team sport athletes (TSAs) are associated when absorbing force, during cutting and landing movements due to a lack of eccentric strength and decreased neuromuscular control leading to excessively higher joint forces. Thus, this project aimed to identify if TSAs had different acceleration and deceleration force profiles compared to a control group (non-TSA) when performing drop jumps (DJs). Methods: University TSAs (n = 15) and non-TSAs (n = 10) performed a series of DJs from a 39 cm box onto a force-plate. All data were normalized to the individual's body mass. Between-group differences in ground reaction force (GRF), rate of force development (RFD), and propulsive and breaking impulses were compared via t-tests and standardized differences. Results: TSAs had significantly, and meaningfully greater RFD than the non-TSAs (p < 0.01, Hedges’ g (ES) = 1.24, 53%). While not statistically significant, the non-TSA group produced practically larger mean GRFs than TSAs (p = .09, ES = 0.72, 12.1%). No significant or meaningful between-group differences were detected for propulsive impulse (p = 0.08, ES = 0.41, 9.1%), braking impulse (p = 0.85, ES = 0.25, 4.6%), or impulse ratio (p = 0.35, ES = 0.21, 6.7%). Conclusions: This study shows the presence of significant RFD differences during the DJ in TSAs compared to non-TSAs. Furthermore, this investigation also showed there was no difference between TSA and students in GRF and impulse metrics. Implications from these findings suggest that TSAs can produce force rapidly, but deceleration metrics were not different from untrained students.